Efeito do exercício agudo de curta duração na atividade da enzima δ-aminolevulinato desidratase em humanos - Schettert, Sally Danuta (2009)
Aerobic exercise of sufficient intensity and duration can result in increased generation of reactive oxygen species and exercise of extreme endurance may cause oxidative stress with a concomitant decreased activity of antioxidant defense systems. The aim of this study was to investigate the possible effect of a peak of oxidative stress exposition on the activity of blood d-ALA-D, an enzyme sensitive to pro-oxidant situations. The protocol of exercise (treadmill) was divided in rest, submaximal exercise, maximal exercise, and recovery. Oxidative stress biomarkers (TBARS production and δ-ALA-D activity), antioxidant defenses systems (catalase activity, -SH and ascorbic acid) were measured in human blood. The maximal exercise induced an increase in TBARS production and -SH levels during submaximal exercise, maximal exercise and recovery when compared with resting. δ-ALA-D activity increased at maximal exercise and recovery when compared with resting. Catalase activity increased during submaximal exercise and recovery when compared to the rest period. The results described here suggest that d-ALA-D was modulated in a way similar to that observed for other biomarkers of oxidative stress. Complementary investigations analyzing the functional role of d-ALA-D activity need to be performed. Additionally, the results suggest that during the test stages the stimulation of antioxidant defense systems (observed by the increase in thiol group levels) were not sufficient to prevent lipid peroxidation even in trained individuals.